2014
DOI: 10.1164/rccm.201306-1088oc
|View full text |Cite
|
Sign up to set email alerts
|

Humidifier Disinfectant–associated Children’s Interstitial Lung Disease

Abstract: This study suggests that humidifier disinfectant inhalation causes an idiopathic type of chILD that is characterized by spontaneous air leak, rapid progression, lack of response to treatment, and high mortality. Further safety studies must be performed on common environmental compounds, particularly those that enter the human body by an unusual route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 33 publications
4
117
0
Order By: Relevance
“…This result is similar to high mortality including 80 deaths (58%) among 138 child interstitial lung disease patients in Korea who were reported to be associated with use of humidifier disinfectant [13]. Preschool-age children definitely develop higher exposure in the home environment than do other family members because they spend much of their time at home.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result is similar to high mortality including 80 deaths (58%) among 138 child interstitial lung disease patients in Korea who were reported to be associated with use of humidifier disinfectant [13]. Preschool-age children definitely develop higher exposure in the home environment than do other family members because they spend much of their time at home.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, this assumption was confirmed by Kim et al [13] who concluded through a nationwide surveillance study in Korea assessing the clinical characteristics of 138 children’s interstitial lung diseases registered between 2006 and 2011, no more new cases had been found two years after the ban of humidifier disinfectant sales.…”
Section: Discussionmentioning
confidence: 75%
“…Humidifier disinfectant-associated chILD, outbreaks of which were originally observed among Korean children in spring 2006, [83][84][85] is characterized by spontaneous air leak, rapid progression, and high mortality. 86,87 Radiologic abnormalities include diffuse or patchy GGO, dense consolidation, and diffuse centrilobular nodules. Lung biopsy reveals a temporally homogeneous pathologic process characterized by variable degrees of bronchiolar injury associated with bronchiolocentric acute lung damage and relative sparing of the lobular periphery, consistent with an inhalation injury.…”
Section: Humidifi Er Disinfectant-associated Childmentioning
confidence: 99%
“…Lung biopsy reveals a temporally homogeneous pathologic process characterized by variable degrees of bronchiolar injury associated with bronchiolocentric acute lung damage and relative sparing of the lobular periphery, consistent with an inhalation injury. 86 Humidifier disinfectant-associated chILD has been eradicated on withdrawal of humidifier disinfectants from the market in November 2011. However, thousands of potentially toxic chemicals (to which children are far more vulnerable than adults) are used worldwide.…”
Section: Humidifi Er Disinfectant-associated Childmentioning
confidence: 99%
“…The article will help in increasing the awareness of ILD in infants and children, and the use of correct diagnostic pathways. We still have much to learn; the recent severe ILD described in Korea [5], attributed to humidifier disinfectant, underscores the need for the pediatric pulmonologist to be aware of new conditions. The lung is exposed to thousands of litres of polluted air per day, and it is small wonder we are still learning new things about what can go wrong.…”
mentioning
confidence: 99%